2015
DOI: 10.1080/10789669.2014.969171
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant transport in membrane based energy recovery ventilators

Abstract: Ventilation systems are used to exhaust stale air and bring fresh air into sealed buildings. To maintain a comfortable indoor environment, this incoming air must be heated or cooled, which consumes energy. Consequently, membrane-based plate-type energy recovery ventilators are a component used in many energy-efficient ventilation systems. In these air-to-air energy recovery ventilator exchangers, incoming and outgoing air streams are passed over opposing sides of a membrane through which heat and moisture are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Furthermore, for RAMEEʼs they found that EATR values are insensitive to changes in airflow rates, liquid desiccant flow rates, latent effectiveness and environmental conditions. Huizing et al 7 reported EATR values observed by previous researchers in their paper. They used CONTAM software to model pollutant transfer rates under different permeabilities of the membrane material.…”
Section: Concluded Thatmentioning
confidence: 77%
See 3 more Smart Citations
“…Furthermore, for RAMEEʼs they found that EATR values are insensitive to changes in airflow rates, liquid desiccant flow rates, latent effectiveness and environmental conditions. Huizing et al 7 reported EATR values observed by previous researchers in their paper. They used CONTAM software to model pollutant transfer rates under different permeabilities of the membrane material.…”
Section: Concluded Thatmentioning
confidence: 77%
“…While ERVs offer the opportunity for energy-efficient ventilation, prior studies indicate that mass transport of contaminants from the exhaust to supply airflow of ERVs are possible for an indoor burst of pollutants due to everyday operations [5][6][7][8] . The mass transport in ERVs is mainly assessed by the factor referred to as exhaust air transfer efficiency (EATR) 5 .…”
Section: Concluded Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern building ventilation systems make use of energy recovery devices instead [6]. A technology which becomes increasingly relevant and popular is what one calls a membrane based enthalpy exchanger [7][8][9][10][11][12]. Such devices ensure an indirect contact of fresh and discharged air via vapor permeable membranes in order to recover sensible as well as latent heat.…”
Section: Introductionmentioning
confidence: 99%